2011
DOI: 10.1097/prs.0b013e31822b6682
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Outcomes in Patients Undergoing Contralateral Prophylactic Mastectomy

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 0 publications
4
53
1
1
Order By: Relevance
“…A CPM has not been shown to provide a definitive survival benefit 4,6,37,38 for all patients and has been associated with increased surgical complications. 17,39,40 Patients also choose CPM to decrease their risk of contralateral breast cancer, but rates of contralateral breast cancer are low. 41 Studies have shown that patients think CPM will improve survival, and they overestimate their contralateral breast cancer risk, 36,42,43 but these studies do not differentiate how race influences these knowledge deficits.…”
Section: Discussionmentioning
confidence: 99%
“…A CPM has not been shown to provide a definitive survival benefit 4,6,37,38 for all patients and has been associated with increased surgical complications. 17,39,40 Patients also choose CPM to decrease their risk of contralateral breast cancer, but rates of contralateral breast cancer are low. 41 Studies have shown that patients think CPM will improve survival, and they overestimate their contralateral breast cancer risk, 36,42,43 but these studies do not differentiate how race influences these knowledge deficits.…”
Section: Discussionmentioning
confidence: 99%
“…), with accuracy verified by a second reviewer (N.I.Z.). The following information regarding each eligible trial was recorded: study reference details (e.g., first author, year of publication), study design, number 14,17,18 ; and flap failure, defined as total flap loss 9,14,17,18 or flap failure. 15,16 Additional complications of interest that were not on this list were noted.…”
Section: Data Extractionmentioning
confidence: 99%
“…Breast reconstruction adds substantially to the morbidity 28 and complications commonly affect the prophylactic side in bilateral mastectomy. 31,32 Whilst in the main, patients selecting CPM are satisfied, a proportion of patients will experience regret, issues with body image, challenges forming sexual relationships and lack feelings of femininity. 46 Moreover, whilst few studies explicitly examine cost-effectiveness of CPM, limited data suggests that CPM adds to net costs.…”
Section: Discussionmentioning
confidence: 99%